Sclerosing variant of well-differentiated testicular liposarcoma: a case report - Amanda L. Aldrighi; Léia R. Mezalira; Luiz Henrique Gehrke; Patrícia M. Pires; Valéria M. Jorge; Raphael G. Rodeghiero; Eduardo B. C. Bicca (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT Testicular cancers are classified in germ cell and non-germ cell tumors, as well as, liposarcomas. We report the case of a patient with a large testicular liposarcoma, submitted to surgical treatment with excision of scrotal pouch and segment of the spermatic cord, and the left testicle, showing a good evolution. This report presents one of the first cases of a sclerosing variant of well-differentiated testicular liposarcoma, large in size and with no association with another cancer. Due to their location, the diagnosis is difficult and unusual. Complete tumor resection and regular medical follow-up show a good prognosis, less recurrence, and little cellular differentiation.